2011
DOI: 10.2965/jwet.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Recirculating Vertical Flow Constructed Wetland for On-Site Sewage Treatment: An Approach for a Sustainable Ecosystem

Abstract: Sewage can be considered one of the richest and most productive waters for crops since it contains nitrogen (5 -7%) and phosphorus (3 -5%) and in constructed wetlands it could be used as fertilizer. The feasibility of growing corn on a recirculating vertical flow constructed wetland (RVFCW) treating sewage on-site was examined. Corn was planted at 107,000 seeds/ha. Effluents from a septic tank and a RVFCW were analyzed for water quality variables. Treatment efficiencies (removal) were high for fecal coliform b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The removal in the calcite filter was initially good, but after three months all P-filters were saturated [20]. Garcia-Perez, A. et al [21] reported 76% for phosphorus removal using gravel as substrate, however they used a recirculating vertical flow constructed wetland growing and harvesting corn, a crop commodity that specifically uses large amount of phosphorus during the growing season. Iron-rich volcanic rock used as support material reached 81% phosphorus removal [17].…”
Section: Resultsmentioning
confidence: 99%
“…The removal in the calcite filter was initially good, but after three months all P-filters were saturated [20]. Garcia-Perez, A. et al [21] reported 76% for phosphorus removal using gravel as substrate, however they used a recirculating vertical flow constructed wetland growing and harvesting corn, a crop commodity that specifically uses large amount of phosphorus during the growing season. Iron-rich volcanic rock used as support material reached 81% phosphorus removal [17].…”
Section: Resultsmentioning
confidence: 99%